Cryptocurrency Adoption in the Developing Countries: Effects on Consumer Trust and Continuance Intention to Adopt - Lian , Song Bee; Falahat , Mohammad; Kiong , Tee Poh (Electronic Journal of Business and Management, 2023)
Cryptocurrency is gaining popularity worldwide and has transformed the global financial markets. Consumers’ adoption of cryptocurrency is increasing, which leads to more attention need to be given to building their trust and continuing intention to adopt cryptocurrency. This study aims to examine the consumers’ adoption of cryptocurrency in developing countries. The antecedents of perceived usefulness, perceived ease of use, perceived risk, and perceived utility are examined on consumer trust and continuance intention to adopt cryptocurrency. The study consists of 410 samples from consumers who have experienced the adoption of cryptocurrency in Malaysia, India, and the Philippines. By using the quantitative method, structural equation modelling (SEM) was utilised to analyse the collected data. The findings confirmed that perceived usefulness, perceived ease of use, perceived risk, and perceived utility have positive effects on consumer trust. Subsequently, consumer trust has a positive effect on the continuance intention to adopt cryptocurrency. In theoretical contributions, the study contributes to the extension of the Technology Acceptance Model (TAM) by adding perceived risk and perceived utility as the antecedents to original elements of perceived usefulness and perceived ease of use. In practical contributions, the findings will help cryptocurrency service providers enhance the consumer adoption of cryptocurrency by building trust elements.